High-Capacity Cells and Batteries for Electric Vehicles - Lluc Canals Casals; Marcel Macarulla; Alberto Gómez-Núñez (Energies, 2021)
The automotive sector is rapidly accelerating its transformation towards electric mobility, and electric vehicle (EV) sales have been increasing year after year since the beginning of the decade [...]